A study on the practices in solid waste management of households in coastal communities in Miag-ao, Iloilo. - Millaro, Raizza A
The study was undertaken to escribe the practices in Solid Waste Management of households in caostal communities of Miag-ao. It genrally aimed to identify and describe the practices of housholds in managing solid waste in coastal communitiesand meet specific objectives by: (2) describing the level of participation of household members on SWM; (3)describing how SWM affects health and sanitation of households in coastal communities; and (4) identifying the government's role in SWM of the coastal communities in Miag-ao. The research design that was used was the descriptive type of design. survey and key informant interview was conducted in gathering the data. The study found out that the househpolds on coastal communities often practiced open burning, open dumping and few practiced composting. The survey revealed that disposal of garbage was the most concern of the households in SWM. Recommendations of the researchers focused on improving socio-cultural, administrative, health and sanitation of the households, and increasing the efficiency to respond to SWM concerns.